2021
DOI: 10.3390/genes12111838
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Novel W2027L Mutation and Non-Target Site Resistance on Acetyl-CoA Carboxylase-Inhibiting Herbicides in a French Lolium multiflorum Population

Abstract: Herbicides that inhibit acetyl-CoA carboxylase (ACCase) are among the few remaining options for the post-emergence control of Lolium species in small grain cereal crops. Here, we determined the mechanism of resistance to ACCase herbicides in a Lolium multiflorum population (HGR) from France. A combined biological and molecular approach detected a novel W2027L ACCase mutation that affects aryloxyphenoxypropionate (FOP) but not cyclohexanedione (DIM) or phenylpyraxoline (DEN) subclasses of ACCase herbicides. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…To date, resistance has unveiled approximately 20 distinct ACCase amino acid substitutions across seven key loci within the CT domain of the plastidic ACCase in Alopecurus myosuroides, associated with herbicide resistance. These substitutions include Ile-1781-Leu/Thr/Val, Trp-1999-Cys/Leu/Ser, Trp-2027-Cys/Leu/Ser, Ile-2041-Asn/Val, Asn-2078-Glu/Gly, Cys-2088-Arg, and Gly-2096-Ala/Ser. , Among these, Ile-1781-Leu is notably prevalent, demonstrating robust resistance across three chemical families of ACCase inhibitor herbicides. Conversely, the Gly-2096-Ser mutation predominantly confers resistance to APP herbicides, with limited exceptions, such as in Phalaris paradoxa, where resistance extends to the CHD herbicide pinoxaden. In this study, three stably inherited herbicide-resistant mutants were identified within three distinct rice EMS mutant populations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, resistance has unveiled approximately 20 distinct ACCase amino acid substitutions across seven key loci within the CT domain of the plastidic ACCase in Alopecurus myosuroides, associated with herbicide resistance. These substitutions include Ile-1781-Leu/Thr/Val, Trp-1999-Cys/Leu/Ser, Trp-2027-Cys/Leu/Ser, Ile-2041-Asn/Val, Asn-2078-Glu/Gly, Cys-2088-Arg, and Gly-2096-Ala/Ser. , Among these, Ile-1781-Leu is notably prevalent, demonstrating robust resistance across three chemical families of ACCase inhibitor herbicides. Conversely, the Gly-2096-Ser mutation predominantly confers resistance to APP herbicides, with limited exceptions, such as in Phalaris paradoxa, where resistance extends to the CHD herbicide pinoxaden. In this study, three stably inherited herbicide-resistant mutants were identified within three distinct rice EMS mutant populations.…”
Section: Discussionmentioning
confidence: 99%
“…Among grasses, Echinochloa ssp. is reported in two articles [ 9 , 14 ] and L. multiflorum in one [ 8 ]; among dicots, two articles reported on the global invasive weed species A. palmeri [ 10 , 13 ]. All these weeds are acknowledged to be among the top 10 weed species resistant to most SoAs globally [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three articles reported mechanisms of TSR nature covering most of the known types: point mutations [ 8 , 9 ], codon deletion [ 10 ], and altered expression patterns [ 9 ].…”
Section: Target-site Resistance Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations